+0  
 
0
71
1
avatar

Solve |x^2 - 3x + 2| = 1.

 Dec 31, 2020
 #1
avatar+816 
0

Hello Guest!

 

Because of absolute value, we have 2 options we need to test out (x^2 - 3x + 2 = 1 and x^2 - 3x + 2 = -1). 

 

Case 1: 

x^2 - 3x + 2 = 1

x^2 - 3x + 1 = 0 (Subract 1 from both sides)

With the quadratic formula, x = 3/2 + sqrt(5)/2 or x = 3/2 - sqrt(5)/2. 

 

Case 2: 

x^2 - 3x + 2 = -1

x^2 - 3x + 3 = 0

If you applied the quadratic formula, there wouldn't be any real answers. 

 

Answer:

x = 3/2 + sqrt(5)/2 or x = 3/2 - sqrt(5)/2. 

 

I hope this helped. :))))

 

=^._.^=

 Dec 31, 2020

48 Online Users

avatar
avatar